Adenomatoid hyperplasia of minor salivary glands: Analysis of proliferative activity and a review of the literature - ARAI, Jiro; KURAGUCHI, Jun; OHUCHI, Tomoyuki; ABIKO, Yoshihiro; NISHIMURA, Michiko; OGAWA, Masaru; KOHAMA, Gen-iku; SAITOH, Masato; SATOH, Masaaki; KAKU, Tohru (Japanese Journal of Oral and Maxillofacial Surgery, 1997)
Adenomatoid hyperplasia is an uncommon clinicopathological entity, which is a non-neoplastic, non-inflammatory enlargement of the minor mucous salivary glands. This lesion presents clinically as an asymptomatic tumor-like nodule that is characterized microscopically by a proliferation of minor salivary gland tissue. Very few reports of this lesion have appeared in the literature, and the proliferative activity of adenomatoid hyperplasias has not been studied previously. The number of argyrophilic nucleolar organizer regions (AgNOR) can be used to study the degree of cell proliferative activity. The mean number of AgNOR increased in a stepwise fashion from normal salivary glands (1.47±0.05) to adenomatoid hyperplasia (1.58±0.05) and pleomorphic adenomas (1.73±0.07). The clinical features also were discussed with a review of the literature.